Calibration of the Tide Gauge at King Edward Point, South Georgia Island - TEFERLE, Felix Norman; HUNEGNAW, Addisu; Woodworth, P L; Foden, P R; Williams, S D P; Hibbert, A; Pugh, J (2015)
After initial sea level observations in the 1950s, a new pressure tide gauge (Global Sea Level Observing System 187) was installed at King Edward Point (KEP), South Georgia Island, British Overseas Territories in the South Atlantic Ocean, in 2008. This was car-ried out as part of the ACCLAIM (Antarctic Circumpolar Current Levels by Altimetry and Island Measurements) programme. In 2013 the KEP Geodetic Observato-ry was established in support of various geoscience applications including the monitor-ing of vertical land movements at KEP. Currently, the observatory consists of two state-of-the-art GNSS stations with local benchmark networks, allowing the height determina-tions from the GNSS antennas to be transferred to the tide gauge and forming a height reference within the International Terrestrial Reference Frame. Finally in 2014, a tide board was added to the tide gauge, which, together with the GNSS and levelling obser-vations, now allows the calibration of the tide gauge. In this study, we will present the results from the calibration of the tide gauge using the GNSS observations from the KEP Geodetic Observatory for the period from February 2013 to present, the levelling campaigns in 2013 and 2014, and geoid undulations de-rived from a seamless combination of the latest GOCO and EGM2008 gravity models. New Geodetic Infrastructure and Reprocessed GPS Solutions for Sea Level, Climate and Geodynamics (GSCG)